FABRICATION AND RELEASE KINETICS OF PIPERAZINE CITRATE TABLETS USING NATURAL GUM - DAS, SUDIPTA; BISWAS, PINKI; DUTTA, CHANDRIMA; BISWAS, DIPTENDU SEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the present study was to formulate the piperazine citrate tablets using natural aloe vera gum as a binding agent and evaluate the tablets. Methods: The extracted aloe vera gum was used for the preparation of piperazine citrate tablets, and the binding characteristics are compared with an equivalent amount of acacia and sodium carboxymethyl cellulose (NaCMC) in different formulations of piperazine citrate tablets. Three batches of piperazine citrate tablets were prepared using acacia (F1), NaCMC (F2), and aloe vera gum (F3) as binding agents. The assessment parameters that are used to evaluate the binding property were the hardness, friability, disintegration time, in vitro dissolution rate, and amount release study. The drug release kinetics of different formulations was determined. Results: The granules were evaluated by determining the angle of repose (25.39±0.13 to 26.23°±0.11°), bulk density (0.567±0.004 to 0.596±0.006 g/cm3), tapped density (0.672±0.006 to 0.717±0.007 g/cm3), Hausner ratio (1.185±0.03 to 1.211±0.016), and Carr’s index (15.62±0.021 to 17.48%±0.009%), which shows a satisfactory flow ability. The tablets were subjected to hardness (3±0.63 to 4±0.82 kg/cm2), friability (0.57±0.01 to 0.75%±0.001% w/w), disintegration time (14.78±0.23 to 20.02±0.11 min), and in vitro release studies. The drug release kinetics of different formulations was determined. Conclusion: As per the results, aloe vera gum has good binding properties and can be preferred over other binders and might be found to be a suitable binder in fast dissolving tablets formulation.